Targeting gut microbiota and metabolism profiles with coated sodium butyrate to ameliorate high-energy and low-protein diet-induced intestinal barrier dysfunction in laying hens - Sasa Miao; Jiankui Li; Ying Chen; Wenyan Zhao; Mengru Xu; Fang Liu; Xiaoting Zou; Xinyang Dong (Animal Nutrition)
High energy diets are a risk factor for intestinal barrier damage. Butyrate, a major energy source for intestinal epithelial cells, has been shown to improve barrier dysfunction and modulate the gut microbiota. In this trial, we examined the preventative effect of coated sodium butyrate (CSB) on high-energy and low-protein (HELP)-induced intestinal barrier injury in laying hens, and also worked to determine the underlying mechanisms by an integrative analysis of gut microbiota and the metabolome. A total of 216 healthy 28-week-old Huafeng laying hens were randomly assigned to 3 groups with 6 replicates each: the CON group (normal diet), HELP group (HELP diet) and CH500 group (500 mg/kg CSB added to HELP diet). The duration of the trial encompassed a period of 10 weeks. The results revealed that CSB treatment improved the laying rate and mitigated the detrimental effects on intestinal barrier function and the inflammatory response induced by the HELP diet in laying hens (P < 0.05). Microbial profiling analysis revealed that the CSB treatment reshaped the HELP-perturbed gut microbiota and promoted the growth of beneficial bacteria (P < 0.05). Untargeted metabolomics analysis revealed that CSB reduced the metabolites associated with intestinal inflammation (P < 0.05). In conclusion, CSB did not merely modulate alterations in the gut microbiota composition and microbial metabolites but also yielded increased egg production, while mitigating intestinal barrier dysfunction and inflammatory responses induced by HELP in laying hens.